Pengaruh Kinerja Keuangan dan Makroekonomi Terhadap Harga Saham Pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Periode 2019 - 2022. - Safalah, Jenni; Paramita, R.A. Sista (Universitas Negeri Surabaya, 2024)
This study aimed to analyse the influence of ROE, DER, EPS, PER, inflation, exchange rate, and world oil price on energy sector companies listed in the Indonesia Stock Exchange period 2019 – 2022. This type of research is causal research, with the data source used is quantitative data. Using a purposive sampling technique, the research sample was taken to obtain 55 samples with criteria for sector energy companies listed on the Indonesia Stock Exchange, consistently reporting financial reports and not carrying out corporate action during the research period. The data analysis technique used in this research is a multiple linear regression method using the IBM SPSS 26 application. Partial results show that ROE, DER and PER do not affect stock prices. Meanwhile, EPS, exchange rates, and world oil prices have a positive effect on stock prices, while inflation has a negative effect on stock prices. Referring to the results of this research, investors are advised to pay more attention to EPS, inflation, exchange rates, and oil price movement, which can help investors make investment decisions on shares in energy sector companies.